Biomechanical Analysis of Running and Dodging Techniques in Kho-Kho : Implications for Injury Prevention and Performance Enhancement - Dr. Veerandra K M (International Journal of Scientific Research in Humanities and Social Sciences, 2025)
Using kinematic and kinetic variables (stride mechanics, ground reaction forces, joint angles, and muscle activation patterns) and with a sample of competitive Kho-Kho players undergoing analysis of their motion, ground reaction forces, and electromyographic (EMG) activity, the present study provides a biomechanical perspective on specific dodging and running techniques employed in the sport for injury prevention or performance benefit through the examination of: (i) optimal sprinting mechanics (e.g., foot strike and hip-knee coordination); (ii) evasion (low center of gravity, rapid lateral weight shifts, and controlled deceleration); and (iii) relationships between distances travelled and time taken to change direction; wherein the results reveal that the dynamics of running and dodging have direct implications on injury pathology and performance and provide specific recommendations in terms of targeted neuromuscular training, plyometric drills, and proprioceptive exercises to optimize biomechanical efficiency and minimize injury susceptibility, highlighting the importance of integrating evidence-based movement correction strategies into Kho-Kho training regimens to maximize agility, minimize injury risk, and enhance overall competitive performance.
Keywords: Biomechanical Analysis; Running Mechanics; Dodging Techniques; Injury Prevention; Performance Enhancement; Kinematic and Kinetic Assessment